Metabolomics comparison of cord and peripheral blood-derived serum eye drops for the treatment of dry eye disease. (August 2021) - Quartieri, Eleonora; Marraccini, Chiara; Merolle, Lucia; Pulcini, Stefano; Buzzi, Marina; Guardi, Manuela; Schiroli, Davide; Baricchi, Roberto; Pertinhez, Thelma A.
Abstract: Allogeneic peripheral blood-derived (PBS) serum eye drops have been largely used in the treatment of dry eye disease (DED). Recently, cord blood has emerged as an effective alternative serum source (cord blood serum, CBS), containing a higher amount of growth factors than PBS, it holds the promise of a better capability to stimulate corneal healing. However, the lack of a standardized method for preparation, dispensation, storage and a poor biochemical characterization still hamper the establishment of a clinical consensus. Here the metabolomes of the two different serum eye drop preparations were compared using proton nuclear magnetic resonance spectroscopy. We found that both PBS and CBS contained several organic compounds, the majority of them already detected in human tears and may be thereby considered lacrimal substitutes. Metabolites having in the multivariate statistical analysis Partial least squares discriminant analysis (PLS-DA) a VIP scores > 1.0 were considered to be significantly different. All the metabolites identified were found to have a p < 0.05 in the univariate analysis. CBS, in particular, showed the highest amount of choline, myo-inositol, glutamine, creatine and β-hydroxybutyrate. These evidences constitute relevant advances towards serum eye drops characterization and confirm that cord blood is a valid alternative source of serum eye drops.